Geographical distribution and disease associations of the CD45 exon 6 138G variant. - Ward, V; Hennig, B; Hirai, K; Tahara, H; Tamori, A; Dawes, R; Saito, M; Bangham, C; Stephens, H; Goldfeld, A; Kunachiwa, W; Leetrakool, N; et al. (2006)
CD45 is crucial for normal lymphocyte signalling, and altered CD45 expression has major effects on immune function. Both mice and humans lacking CD45 expression are severely immunodeficient, and single-nucleotide polymorphisms in the CD45 gene that cause altered splicing have been associated with autoimmune and infectious diseases. Recently, we identified an exon 6 A138G polymorphism resulting in an increased proportion of activated CD45RO T cells and altered immune function. Here we report a significantly reduced frequency of the 138G allele in hepatitis C Japanese patients and a possibly reduced frequency in type I diabetes. The allele is widely distributed in the Far East and India, indicating that it may have a significant effect on disease burden in a large part of the human population.